2000
DOI: 10.1054/bjoc.1999.0997
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemotherapy with interleukin-2, interferon- α and 5-fluorouracil for progressive metastatic renal cell carcinoma: a multicenter phase II study

Abstract: In patients with metastatic renal cell carcinoma response rates of 7–26% have been achieved with immunotherapy. A high response rate of 48% in 35 patients has been reported for treatment with the combination of interferon-α (IFN-α), interleukin-2 (IL-2) and 5-fluorouracil (5-FU) (Atzpodien et al (1993 a ) Eur J Cancer 29A : S6–8). We conducted a multicentre phase II study to confirm these results. Metastatic renal cell carcinoma patients were treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…This protocol is closely related to the schedule designed for other clinical research trials with IL-2, IFNa and 75-FU within the framework of the French Immunotherapy Group Négrier et al, 2000). These large studies showed an unexpectedly low response rate Négrier et al, 2000) like the present study, compared to more promising results obtained by others (Atzpodien et al, 1993;Hofmockel et al, 1996;Joffe et al, 1996;Ellerhorst et al, 1997;Tourani et al, 1998;Allen et al, 2000;Dutcher et al, 2000;Elias et al, 2000;van Herpen et al, 2000).…”
Section: Discussionsupporting
confidence: 66%
“…This protocol is closely related to the schedule designed for other clinical research trials with IL-2, IFNa and 75-FU within the framework of the French Immunotherapy Group Négrier et al, 2000). These large studies showed an unexpectedly low response rate Négrier et al, 2000) like the present study, compared to more promising results obtained by others (Atzpodien et al, 1993;Hofmockel et al, 1996;Joffe et al, 1996;Ellerhorst et al, 1997;Tourani et al, 1998;Allen et al, 2000;Dutcher et al, 2000;Elias et al, 2000;van Herpen et al, 2000).…”
Section: Discussionsupporting
confidence: 66%
“…Since many of our subject samples had undergone metastatectomy prior to immunochemotherapy, it is possible that those who would have shown responses to subsequent systemic therapy may have been masked by prior surgery. On the other hand, there have been others who have similarly reported lower response rates for the triple therapy compared with our results [1,27] . Although it is one of the most widely used systemic treatment for metastatic renal cell carcinoma, controversy still exists regarding the actual effi cacy of triple combination immunochemotherapy, and it is still considered as more of a palliative approach of treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Response rates remain low at around 15%, and the toxicity of high-dose IL-2 limits its use (Krown, 1987;Muss, 1998;Kammula, 1998;van Herpen et al, 2000). Targeted therapeutics are relatively new to the oncology field, most acting via the inhibition of mitotic signalling kinases.…”
mentioning
confidence: 99%